Business ethics now - Ghillyer, Andrew (Dubuque : McGraw-Hill Education, 2021)
"This book helps us in undertsanding ethics, business ethics and organizational ethics, issues relating to business ethics and the key players involved. It explains the challenges involved in developing an ethical culture within an organization and what lies ahead for companies as they grow on an international and global scale"--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Business ethics